APPLICATION OF THE PROBLEM-BASED LEARNING MODEL TO IMPROVING STUDENTS' LEARNING OUTCOMES IN UNDERSTANDING READING TEXT - Fatoni, Ahmad (Jurnal Primary (Kajian Ilmu Pendidikan Dasar dan Humaniora), 2023)
Abstrack Based on the results of observations made there was a lack of students' ability to understand reading text, therefore a class action research was carried out on the application of the problem based learning model to improving student learning outcomes in understanding reading texts. The purpose of this study was to find out how the application of the problem-based learning model to improving student learning outcomes in understanding reading content in class V-B SDN 138 Gegerkalong Girang. This research uses Collaborative Classroom Action Research (PTKK) with the Kurt Lewin model design, Collaborative Classroom Action Research (PTKK) uses three cycles. With research steps in the form of planning, action, observation, and reflection. data collection techniques using observation and learning achievement tests, as well as using qualitative descriptive analysis techniques. The results of the study show that the problem-based learning model can improve Indonesian language learning outcomes in understanding the content of reading texts in class V-B SDN 138 Gegerkalong Girang Bandung city. This is indicated by the increase in the average value of student learning outcomes increasing starting in cycle I 17 (68%) students who complete and students who do not complete 8 (32%) students with an average score (74.20), cycle II 19 (76%) students who completed and students who did not complete 6 students with an average score (80.00), and cycle III 23 (92%) students who completed and students who did not complete 2 students with an average score (84.00). Keywords: PBL, Learning Outcomes, Reading